Health care systems as determinants of outcomes in multiple myeloma: final results from the Latin American MYLACRE study - Hungria, Vania; Gaiolla, Rafael [UNESP]; Galvez, Kenny; Remaggi, Guillermina; Schutz, Natalia; Bittencourt, Rosane; Maiolino, Angelo; Quintero-Vega, Guillermo; Cugliari, Maria Silvana; Braga, Walter Moises Tobias; Villarim, Carolina Colaco; Crusoe, Edvan; et al. (American Society of Hematology, 2025)
Although systemic therapy for multiple myeloma (MM) has evolved considerably over the past 2 decades, state-of-the-art treatment is not uniformly available in Latin America. In some countries, disparities between the public and private sectors in clinical presentation, access to novel agents, and transplantation are striking, with the public sector lagging. We conducted a multicenter, observational study of patients with MM in 5 Latin American countries (Argentina, Brazil, Colombia, Mexico, and Panama). We enrolled patients aged ≥18 years diagnosed with MM between January 2016 and June 2021, using data collected between May 2019 and June 2022. We categorized institutions as “public” when primarily funded by federal or local government, and “private” when financed mostly or completely by other sources. We analyzed 1029 patients, 1021 of whom could be classified into public (n = 339) and private (n = 682) institutions. These 2 groups differed in many respects, with patients from the latter having better baseline prognostic features (including eligibility to transplantation) and receiving combinations of immunomodulatory drugs and proteasome inhibitors, as well as anti-CD38 antibodies, more frequently than patients from public institutions. Among 960 patients with complete data for this analysis, the median overall survival was 44.6 months in public institutions and 53.3 months in private institutions (hazard ratio, 0.84; 95% confidence interval, 0.67-1.04; P = .109). Our results indicate diagnostic and therapeutic shortcomings in the management of MM in Latin America, with important gaps in patient profile, treatment patterns and long-term outcomes between public and private institutions. This trial was registered at www.clinicaltrials.gov as #NCT03955900.